Protective Ceramic Coatings for Solid Oxide Fuel Cell (SOFC) Balance-of-Plant Components - Raymond L. Winter; Prabhakar Singh; Mark K. King; Manoj K. Mahapatra; Uma Sampathkumaran (Advances in Materials Science and Engineering)
Solid oxide fuel cells (SOFCs) have the potential to meet the growing need for electrical power generation if the cost per megawatt can be further reduced. Currently, SOFC stacks are replaced too frequently to be cost competitive. SOFC service life can be extended by preventing chromium- (Cr-) bearing species from evaporating from the interior surfaces of balance of plant (BOP) components and poisoning the cathode to increase the lifetime. We have developed yttria-stabilized zirconia (YSZ) and aluminum oxide- (Al2O3-) modified sol-gel paints or inks for coating BOP components. 430 stainless steel (430SS) substrates with three surface conditions were coated with the 0.8–1.5 µm thick YSZ and Al2O3 paints. The coated 430SS samples were tested for thermal cycling resistance, thermal soak, and Cr evaporation. Thermal soak and thermal cycling test results show promise for the YSZ-coated 430SS substrates. The Cr evaporation test of a coated substrate showed a 51% reduction in Cr generation, when compared with a bare substrate.